Highlighting Soft Drinks Consumption in Lebanon (Asian Journal of Social Science Studies, 2024)
This paper aims to highlight the excess consumption of carbonated soft drinks among the Lebanese population and consequently present a call for moderation and reduced consumption (Controlled consumption). A quantitative analysis with a positivist philosophy and a deductive approach is adopted. A questionnaire was administered to 1,612 participants based on their willingness to provide input. Descriptive analysis is used based on the IBM SPSS version 26.0 software. In addition, cross-tabulations were run with Chi-square testing, and a nonparametric Kruskal-Wallis test was also applied to study differences in medians between selected variables. Results illustrate that compared to other nations, Lebanon is a less-than-average consumer of soft drinks (45.5 liters per person per year), with a large percentage of soft drink consumers being young adults and middle-aged adults in the range of 17 to 48 years. This research shows that women consume fewer soft drink glasses than men with averages of 3.82 glasses per week (49.66 liters/yr.) for men and 3.18 glasses per week (41.34 liters/yr.) for women. Results also show no statistically significant relationship between having a job or living status and consuming soft drinks with snacks or food at restaurants. However, the relationship between gender and consuming soft drinks with snacks or food at restaurants is significant (p < 5%). In addition, 17.1% of the participants declared they would never quit consuming soft drinks. Moreover, 85% of females and 79.4% of males have a very good level of health issues awareness about the harms soft drinks cause. Findings also show a significant relation (p < 5%) between gender and awareness.